Abnormal coronary vasomotility in subjects with normal coronary arteries and reduced reserve of coronary flow - Bortone, A; Hess, O M; Gaglione, A; Locuratolo, N; Musci, S; Sebastiani, M; Rizzon, P; Chiddo, A (Cardiologia (Rome, Italy), 1989)
A reduced coronary flow reserve has been reported in patients with ischemia-like symptoms and normal coronary arteries. In 13 such subjects both coronary vasomotion and flow reserve were studied. The luminal area of the proximal and distal third of the left anterior descending and left circumflex artery were determined by biplane quantitative coronary arteriography using a computer-assisted system. Subjects were studied at rest, during submaximal supine bicycle exercise (4.0 min, 116 W) and 5 min after sublingual administration of 1.6 mg nitroglycerin. Heart rate, mean pulmonary and aortic pressure as well as the percent change of both proximal and distal luminal area were determined. In 10 of the 13 subjects, coronary sinus blood flow was measured by coronary sinus thermodilution technique at rest and after dipyridamole infusion (0.5 mg/Kg in 15 min) 10 +/- 5 days after quantitative coronary arteriography. Coronary flow ratio (dipyridamole/rest) and coronary resistance ratio (rest/dipyridamole) were determined in these subjects. Subjects were divided into 2 groups according to the behaviour of the coronary vessels during exercise (vasodilation = Group 1, vasoconstriction = Group 2). Coronary vasodilation of the proximal (luminal area + 26%; p less than 0.001) and distal (+ 45%; p less than 0.001) artery was observed in 7 subjects (Group 1) during exercise and after sublingual nitroglycerin (+46%; p less than 0.001 and +99%; p less than 0.001, respectively). In Group 2 (n = 6), however, there was coronary vasoconstriction of the distal vessel segments (-24%; p less than 0.001) during exercise, whereas the proximal coronary artery showed vasodilation (+ 26%; p less than 0.001) during exercise. Following sublingual nitroglycerin, both vessel segments elicited vasodilation (distal coronary + 44%; p less than 0.001, proximal coronary artery +47%; p less than 0.001). Coronary flow ratio amounted to 2.5 in Group 1 and to 1.2 in Group 2 (p less than 0.05) and coronary resistance ratio to 2.7 in Group 1 and to 1.2 in Group 2 (p less than 0.05), respectively. Thus, among subjects with ischemia-like symptoms and normal coronary arteries there is a subgroup of patients (Group 2) with an abnormal dilator response of the distal coronary arteries to the physiologic dilator stimulus of exercise and a reduced dilator capacity of the resistance vessels after dipyridamole (= abnormal coronary vasodilator syndrome). The nature of this exercise-induced distal coronary vasoconstriction is not clear but might be due to an abnormal neurohumoral tone which may cause or contribute to the blunted vascular response during exercise.